Using Oil Palm Segregation Genetics to Decipher Illegitimate Seed Distribution Channels to Smallholder Farmers in Cameroon - Walter Ajambang Nchu; Paul Koona (Agrotech Journal, 2020)
Planting material or seed is the most determinant factor for oil palm productivity alongside agro climatological and management considerations. A study was conducted to determine the different varieties of oil palm planted in smallholders’ plantations, the distribution channels for oil palm seeds and all the actors involved in the seed trade sector in Cameroon. This is a bid to secure the supply of only improved planting materials to smallholder farmers. 230 oil palm smallholder plantations were surveyed and individual palms were subjected to varietal determination. The Chi-Square Test (c2) for Fixed Ratio Hypothesis (= 0.05) was used to determine whether the observed ratio deviates significantly from the Mendelian hypothesized genetic segregation ratio. Up to 65% of smallholder farms were found to be planted with poor planting material distributed in the different Mendelian ratios; 100% Dura, 50% Tenera and 50% Dura (1:1), 25% Dura, 50% Tenera and 25% Pisifera (1:2:1). The source of this poor quality planting material for these farms was deduced to come from private nursery entrepreneurs and workers of industrial plantations such as the Cameroon Development Corporation (CDC), Cameroon Palm Oil Company (SOCAPALM), Common Initiative Groups (CIG’s) and Non-Governmental Organisations (NGO’s). Farmers supplied by government services especially the Ministry of Agriculture and Rural Development and some of its specialized development projects all received good quality material. Thus, this is the only means now available which can assure the distribution of seeds good quality seeds